2021
DOI: 10.12998/wjcc.v9.i33.10382
|View full text |Cite
|
Sign up to set email alerts
|

Heart failure as an adverse effect of infliximab for Crohn's disease: A case report and review of the literature

Abstract: BACKGROUND Anti-tumor necrosis factor agents were the first biologic therapy approved for the management of Crohn's disease (CD). Heart failure (HF) is a rare but potential adverse effect of these medications. The objective of this report is to describe a patient with CD who developed HF after the use of infliximab. CASE SUMMARY A 50-year-old woman with a history of hypertension and diabetes presented with abdominal pain, diarrhea, and weight loss. Colonoscopy and enter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Based on inclusion and exclusion criteria, the sample size was refined to a slightly smaller size so that a similar study with more prominent participants is recommended for a firm decision regarding anti-TNF utilization. More studies exhibit priming of the cardiac complications in a short period after anti-TNF (12,13), which was the basis of the current perusal sketch; hence, a resemble inquiry with a long-term follow-up is suggested.…”
Section: Strengths and Limitationsmentioning
confidence: 90%
“…Based on inclusion and exclusion criteria, the sample size was refined to a slightly smaller size so that a similar study with more prominent participants is recommended for a firm decision regarding anti-TNF utilization. More studies exhibit priming of the cardiac complications in a short period after anti-TNF (12,13), which was the basis of the current perusal sketch; hence, a resemble inquiry with a long-term follow-up is suggested.…”
Section: Strengths and Limitationsmentioning
confidence: 90%
“…The classification of heart failure severity refers to the NYHA classification, respondents in the study showed the level of NYHA III and IV, which means limited activity with light to reduce the elasticity of the heart arteries, causing damage to the heart [31]. The patient received treatment with diuretics is dominated for HF and showed improvement of symptoms and cardiac function [32].…”
Section: Characteristics Of Respondents From the Studymentioning
confidence: 98%
“…Furthermore, a case of sudden death after receiving a single infusion of infliximab 200 mg in a patient without CHF was reported [157]. Another case report described a patient with CD who developed CHF after infliximab treatment [158]. Recently, a case report presents a patient with relapsing hidradenitis suppurativa who was diagnosed with decompensated CHF after receiving adalimumab during hospitalization [159].…”
Section: Tnf-α Inhibitorsmentioning
confidence: 99%